Prevalence and determinants of complementary and alternative medicine use among infertile patients in Lebanon: a cross sectional study - Ghazeeri Ghina S; Awwad Johnny T; Alameddine Mohamad; Younes Zeina MH; Naja Farah (BMC, 2012)
Abstract Background Complementary and alternative medicine (CAM) is widely used for the treatment of infertility. While the Middle East and North Africa region has been shown to house one of the fastest growing markets of CAM products in the world, research describing the use of CAM therapies among Middle-Eastern infertile patients is minimal. The aim of this study is to examine the prevalence, characteristics and determinants of CAM use among infertile patients in Lebanon. Methods A cross sectional survey design was used to carry out face-to-face interviews with 213 consecutive patients attending the Assisted Reproductive Unit at a major academic medical center in Beirut. The questionnaire comprised three sections: socio-demographic and lifestyle characteristics, infertility-related aspects and information on CAM use. The main outcome measure was the use of CAM modalities for infertility treatment. Determinants of CAM use were assessed through the logistic regression method. Results Overall, 41% of interviewed patients reported using a CAM modality at least once for their infertility. There was a differential by gender in the most commonly used CAM therapies; where males mostly used functional foods (e.g. honey & nuts) (82.9%) while females mostly relied on spiritual healing/prayer (56.5%). Factors associated with CAM use were higher household income (OR: 0.305, 95% CI: 0.132-0.703) and sex, with females using less CAM than males (OR: 0.12, 95% CI: 0.051-0.278). The older patients were diagnosed with infertility, the lower the odds of CAM use (p for trend <0.05). Almost half of the participants (48%) were advised on CAM use by their friends, and only 13% reported CAM use to their physician. Conclusions The considerably high use of CAM modalities among Lebanese infertile patients, added to a poor CAM use disclosure to physicians, underscore the need to integrate CAM into the education and training of health professionals, as well as enhance infertile patients' awareness on safe use of CAM products.